2016
DOI: 10.1111/1744-7917.12319
|View full text |Cite
|
Sign up to set email alerts
|

Controlling infestation of a chocolate factory by Plodia interpunctella by combining mating disruption and the parasitoid Habrobracon hebetor

Abstract: A field experiment of 4 years' duration was carried out to evaluate the efficacy of combining the mating disruption (MD) formulation Dismate ZETA ((9Z,12E)-tetradecadienyl acetate), with the parasitoid Habrobracon hebetor against the Indianmeal moth Plodia interpunctella in a chocolate factory. The experimental period began early in 2011 and ended in late 2014. Begane Dismate dispensers were placed in the facility from 2011 to 2014 and H. hebetor was released in 2014. Pheromone-baited traps were used to monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The use of H. hebetor with Trichogramma evanescens Westwood (Hymenoptera: Trichogrammatidae) against E. kuehniella and P. interpunctella in organic bakeries and mills in Germany and Austria has been demonstrated to be effective [90]. The combined use of H. hebetor and mating disruption (MD) to manage P. interpunctella populations in a chocolate factory (about 2000 m 2 area and 5 m height) decreased moths captured on traps [91]. In a peanut stock warehouse, the release of H. hebetor alone resulted in the 66.1% and 97.3% reduction of P. interpunctella and C. cautella, respectively [92].…”
Section: Commercial Applications Of Parasitoids and Integration Wimentioning
confidence: 99%
“…The use of H. hebetor with Trichogramma evanescens Westwood (Hymenoptera: Trichogrammatidae) against E. kuehniella and P. interpunctella in organic bakeries and mills in Germany and Austria has been demonstrated to be effective [90]. The combined use of H. hebetor and mating disruption (MD) to manage P. interpunctella populations in a chocolate factory (about 2000 m 2 area and 5 m height) decreased moths captured on traps [91]. In a peanut stock warehouse, the release of H. hebetor alone resulted in the 66.1% and 97.3% reduction of P. interpunctella and C. cautella, respectively [92].…”
Section: Commercial Applications Of Parasitoids and Integration Wimentioning
confidence: 99%
“…The effectiveness of H. hebetor has already been recorded, in the control of P. interpunctella in releases inside a chocolate factory for four years [22]. The authors observed that the presence of H. hebetor reduced Brazilian Archives of Biology and Technology.…”
Section: Discussionmentioning
confidence: 96%
“…Its control ability has already been evaluated on many moth species like E. elutella, E. kuehniella, E. cautella, Plodia interpunctella (Hübner), Corcyra cephalonica (Stainton) (Lepidoptera: Pyralidae) and Sitotroga cerealella (Olivier) (Lepidoptera: Gelechiidae) in different products and storage environments, either alone or in combination with other parasitoids [11,15]. Studies were conducted in the storage of bulk wheat [16,17], bulk peanuts [18], packaged cornmeal and rice [19,20], bakeries and mills [21], and chocolate factories [22]. The authors considered aspects such as parasitism rate, number of pest adults captured in the traps, number and frequency of releases and search capacity to determine the efficiency of the parasitoid.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, future stored-product protection combinations of repellents and attractants may also be used in pushpull tactics [6]. Recently, combined action of mating disruption and parasitoid activity Habrobracon hebetor against P. interpunctella in a chocolate factory was reported by Trematerra et al [14].…”
mentioning
confidence: 99%